KEBIASAAN SARAPAN DAN ASUPAN ZAT GIZI DENGAN KADAR HEMOGLOBIN PADA MAHASISWI - Cerdasari, Carissa (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Anemia, characterized by low hemoglobin (Hb) level in woman, including female students, is still a nutritional problem in Indonesia. If it is not immediately treated, anemia can trigger other nutritional problems in mother, infants, and children. This observational cross-sectional study aimed to analyze the relationship between breakfast-eating habits and nutrient intake with hemoglobin level in female students, involving 60 samples, which were selected using purposive sampling. Hb levels were measured using the cyanmethemoglobin method, breakfast-eating habit collected by questionnaire, and nutrients intake was measured using a 3x24 hour food recall. T and Mann-Whitney test were used to analyze the data. There was no relationship (p more than 0.05) between breakfast habits , intake of energy, protein , iron , vitamin A, folic acid, vitamin B12, and vitamin C with Hb level. Although it did not show a significant relationship, there was a tendency for higher intake of energy, iron, and vitamin C in students with normal Hb levels. The lack of relationship between breakfast habits and nutrient intake with Hb levels may indicate other factor that affect female students’ Hb levels.